Kontribusi Pemikiran Muhammad Syahrur Tentang Teori Hudud Dalam Pembaruan Pemikiran Islam - Zuyyina Candra Kirana; Aswadi; Ali Muchasan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Awareness of the importance of updating Islamic legal thought is increasing, it is triggered by the fact that Islamic law that exists today is considered unable to respond to various problems that arise and develop in the modern world. As a result, Islamic law is seen or considered no longer compatible with the times and itis contrary to the doctrine or belief that Islam is a plenary religion that will always be in harmony with the development of the times It emerged that one of the great thinkers in the contemporary era of Muhammad Syahrur introduced a new theory of careful and profound interpretation of the Koran called the Hudud theory. Anapproach in ijtihad (interpretation of individuals) to study the verses of muhkam from the Koran. The term boundary (hudûd) used by Shahrur refers to themeaning of